(untitled) (European Bison Conservation Newsletter, 2022)
Based on long-term data, the process of formation and the current state of free-ranging population of the E. bison “Volozhynskaya” living in the largest woodland of the central part of Belarus is described. In 18 years, the population increased from 15 to 79 individuals, with the average annual growth of 10.1%. Numbers of E. bison, despite a tendency towards the decrease in growth rate, in short time have reached an optimal level and maintain positive dynamics. Annually, on the average six calves are born, and the coefficient of birth rate is at the level typical for Belarus. The coefficient of fertility is by 50% lower comparing to the beginning of population formation. In 2012 three adult males were poached which negatively influenced the population development. General losses (including eliminations) amounted to 44 individuals, including 19 animals of low reproductive value. The prospects of development and use of resources of free-ranging population of the E. bison are described.